2023
DOI: 10.3899/jrheum.220851
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Disease-Specific Risk Factors for Cardiovascular Events in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: A Multinational Retrospective Study

Abstract: ObjectiveTo investigate the occurrence of cardiovascular events (CVE) in a large cohort of patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) across the European Union, China, Turkey, Russia, UK, and USA.MethodsPatients with a definite diagnosis of AAV who were followed ≥3 months and had sufficient documentation were included. Data on myocardial infarction (MI) and stroke were collected retrospectively from tertiary vasculitis centers. Univariate and multivariate Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…25 In summary, AAV is clearly associated with increased CVD. The study by Moiseev et al 4 corroborates this and provides evidence that traditional and kidney-specific factors are independently associated with CVD. Although major gaps exist in CVD risk stratification in AAV, both healthcare professionals and patients should be aware that treatment of modifiable risk factors is necessary.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…25 In summary, AAV is clearly associated with increased CVD. The study by Moiseev et al 4 corroborates this and provides evidence that traditional and kidney-specific factors are independently associated with CVD. Although major gaps exist in CVD risk stratification in AAV, both healthcare professionals and patients should be aware that treatment of modifiable risk factors is necessary.…”
mentioning
confidence: 59%
“…Indeed, Moiseev et al found that 47.6% of their patients with AAV had hypertension. 4 Whereas immunosuppressive drugs such as mycophenolate mofetil may result in an antihypertensive effect, 17 this was not found for avacopan in the ADVOCATE study. 18 Because of its superior antiproteinuric effect and nephroprotective effect, blockade of the RAAS in combination with (moderate) dietary sodium restriction is the first choice for hypertension treatment in AAV with renal involvement.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…В отличие от системных васкулитов с преимущественным поражением мелких сосудов, АТ обычно не сопровождается развитием гломерулонефрита или тубу- [17]. Помимо этого, высокие темпы прогрессирования атеросклероза, сопровождающегося высоким риском сердечно-сосудистых осложнений, характерны не только для АТ, но и других системных васкулитов, в частности АНЦА-ассоциированных [18][19][20][21].…”
Section: Discussionunclassified